Deconstructing Superorganisms and Societies to Address Big Questions in Biology. (November 2017) - Kennedy, Patrick; Baron, Gemma; Qiu, Bitao; Freitak, Dalial; Helanterä, Heikki; Hunt, Edmund R.; Manfredini, Fabio; O'Shea-Wheller, Thomas; Patalano, Solenn; Pull, Christopher D.; Sasaki, Takao; Taylor, Daisy; et al.
Abstract : Social insect societies are long-standing models for understanding social behaviour and evolution. Unlike other advanced biological societies (such as the multicellular body), the component parts of social insect societies can be easily deconstructed and manipulated. Recent methodological and theoretical innovations have exploited this trait to address an expanded range of biological questions. We illustrate the broadening range of biological insight coming from social insect biology with four examples. These new frontiers promote open-minded, interdisciplinary exploration of one of the richest and most complex of biological phenomena: sociality. Trends: Many social insect colonies are closely analogous to multicellular organisms, possessing key 'organismal' traits. Most prominently amongst these is the obligate differentiation of individuals into germ and soma, accompanied by extreme levels of functional integration and a colony-level immune system. This striking echo in evolution means that social insects can provide highly accessible models for questions that have traditionally been the domain of whole-organism and cell biology. The expanded scope of model organisms amongst the social insects, novel techniques and recent conceptual advances suggest that social insect biology can make profound contributions to diverse fields – from immunology to the study of heredity itself – to which it has previously had little connection.